Use of Information and Communication Technology (ICT) for Effective Open and Distant Learning (ODL) - Shah, Attaullah; Khan, Salimaullah (International Journal of Emerging Technologies in Learning (iJET), 2009)
Allama Iqbal Open University (AIOU), Pakistan is one of the sixteen mega-open universities in the world, providing education opportunities to about one million students in Pakistan and the Middle East, from elementary level to doctoral level. The University has been facing quality issues in Open and Distance Learning (ODL) education, mainly due to the poor interaction between tutors and students, outdated course content, a biased assessment system, and lack of trained Human Resource. A major project to improve the quality of education at AIOU has been developed for the technological transformation of this unique national institution with the assistance of the Higher Education Commission of Pakistan. This paper discusses the technological and E-learning Model being implemented for the effective, responsive and target oriented Open and Distant Learning (ODL) at the University.